Human cervix: an alternative substrate for detecting circulating pemphigus antibodies - Leena Chularojanamontri (2018)
© 2016, Springer-Verlag Berlin Heidelberg. Monkey esophagus (ME) is a well-accepted substrate for diagnosing pemphigus vulgaris (PV) by indirect immunofluorescence (IIF). However, its availability is sometimes limited due to ethical concerns. This study aimed to investigate the usefulness of human cervix (HC) as a substrate in the diagnosis of PV by IIF. Initially, serum from 1 PV patient was incubated with tissues from 48 HCs. Median IIF titers on HCs that had different demographic and clinical characteristics were compared. Sera from 5 PV patients were then incubated with ME and 21 HCs. For each serum, the titer of IIF on HC that was not different from ME by more than two-fold dilutions was acceptable. Last, sera from 42 PV, 14 pemphigus foliaceous, and 62 non-pemphigus patients were used to evaluate sensitivity and specificity. The results demonstrate that differences in demographic data among HCs did not affect IIF titers. Titers obtained from ME and HC were comparable (81–100 % acceptable values). Sensitivity of HC for diagnosis of PV was better than for diagnosis of pemphigus foliaceus (90.5 and 71.4 %, respectively). Specificity for PV and PF was 96.2 %. We proposed that HC substrate can be used as an alternative substrate for diagnosis of PV by IIF.